ANALISIS DINAMIKA INTERAKSI SOSIAL DAN PROBLEMATIKA PESERTA DIDIK DI SMAN 1 SRENGAT - Keisya Dini Milan Sari; Muchammad Survy Nur Huda; Muhammad Yahya Maulida Fahmi; Surayanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the dynamics of social interaction and the social problems experienced by students at SMAN 1 Srengat. This research employed a qualitative descriptive approach, utilizing data collection techniques that included interviews with homeroom teachers and the distribution of questionnaires to students. The results showed that students’ social interactions generally developed positively, as reflected in their ability to adapt, cooperate, and communicate within the school environment. The questionnaire results also indicated that most students felt comfortable interacting with peers and were able to establish positive social relationships. However, several social problems were still found, such as low self-confidence, peer pressure, the influence of social media, bullying, and emotional difficulties in social situations. Factors influencing students’ social interactions included family background, economic conditions, peer environment, and the use of gadgets and social media. In response to these issues, the school implemented various efforts such as character education, counseling guidance, extracurricular activities, literacy programs, and restrictions on gadget use during learning activities. Overall, collaboration between schools, teachers, parents, and the social environment is essential in supporting the optimal social development of students in the digital era.